1984
DOI: 10.1017/s0033291700015270
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among psychiatric patients of a district general hospital

Abstract: SynopsisTwenty-two psychiatric patients who committed suicide while receiving hospital treatment or within 3 months of discharge from psychiatric care were studied using general population statistics, a random sample of 100 psychiatric patients and a control group matched individually with the hospital suicides. The rate of suicide among psychiatric in-patients was over 50 times that in the general population. A higher vulnerability to suicide was detected among in-patients (v. other patient groups), men (v. w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 36 publications
1
18
1
1
Order By: Relevance
“…Results showed that patients in the early suicide group had more previous DSH incidents than the late and control groups. Fernando and Storm [11] also examined patients who died by suicide within 3 months of discharge. Their results matched those of McKenzie and Wurr [8], with more DSH histories found in individuals who died by suicide [11].…”
Section: Suicidal Historymentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that patients in the early suicide group had more previous DSH incidents than the late and control groups. Fernando and Storm [11] also examined patients who died by suicide within 3 months of discharge. Their results matched those of McKenzie and Wurr [8], with more DSH histories found in individuals who died by suicide [11].…”
Section: Suicidal Historymentioning
confidence: 99%
“…Several studies comparing suicides within 1 year of discharge with those who did not die by suicide postdischarge found suicide ideation/attempt before admission to be a predictor of completed suicide [1,3,10,11]. Results also revealed that a self-harm/suicide attempt during admission was a significant predictor of suicide [1,8,11]. Results for these variables are summarized in Table 1.…”
Section: Suicidal Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, suicide rates appear to increase with age (Surtees and Duy, 1989), although in some studies suicide rates in women peak at menopause and decline thereafter (Woodbury et al, 1988). Suicide rates among psychiatric inpatients are higher than in the general population (Farberow et al, 1971;Fernando and Storm, 1984;Modestin and Homan, 1989) and may have increased in recent years (Beskow, 1987;Wolfersdorf et al, 1988). These factors suggest that suicide rates among psychogeriatric inpatients may be high.…”
mentioning
confidence: 99%
“…Le taux de suicide d'anciens combattants hospitalisés en milieu médico-chirurgical et neuro-psychiatrique est respectivement 3,5 et 30 fois plus élevé que celui de la population générale (Farberow, 1981). Par rapport à la population générale, on a rapporté en ex-Allemagne fédérale dix fois plus de suicide de patients hospitalisés (WoIfersdorf et al, 1991) et 50 fois plus parmi la clientèle psychiatrique d'un hôpital londonien (Fernando et Storm, 1984).…”
Section: Description Du Suicide De Patients Hospitalisés Fréquenceunclassified